EKSPERIMEN PEMBUATAN SATE TAICHAN KUAH TONGSENG - Puput Dewi Anggraeni (Politeknik Harapan Bersama, 2023)
Satay is one of the mainstays of Indonesian cuisine which has more than one type, such as Madura satay, Padang satay, Klatak satay, and other types of satay. One of the satays that is currently in great demand is